Aplikasi Penjualan Mobil Berbasis Web pada PT KIA Mobil Dinamika Cabang Bintaro dengan Metode Analytical Hierarchy Process (AHP) - Cristian, Aditya; Nurcahyo, Widyat; Faizah, NM (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
PT Mobil KIA Indonesia in Bintaro is engaged in automotive sales, targeting middle- to upper-class consumers with stable economic backgrounds. The company offers various car brands imported directly from Korea to meet the demands of this market segment. However, customers often face challenges in selecting a vehicle that matches their personal criteria due to limited information provided in conventional formats. To address this, a web-based sales system utilizing the Analytical Hierarchy Process (AHP) method is required, allowing customers to access detailed information anytime and anywhere. This system not only aids customers by offering recommendations based on their specified criteria but also supports a structured decision-making process in selecting suitable vehicles. By implementing this system, customers are better equipped to make informed decisions that align with their preferences, thereby enhancing their overall purchasing experience and satisfaction.